A kind of aging-resistant low-toxic natural latex composite material and its preparation method and application

By using specific types of vulcanization accelerators in natural latex, the problem of carcinogens generated during vulcanization is solved, and the aging resistance is improved, achieving the dual improvement of low toxicity and aging resistance of natural latex composite materials.

CN116063751BActive Publication Date: 2025-03-25GUANGDONG KINGFA TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211729170.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-25
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

Existing natural latex products may produce the carcinogen N-nitrosamine during the vulcanization process, resulting in high toxicity and insufficient vulcanization leads to aging resistance deterioration.

Method used

Add appropriate vulcanization accelerators, such as dithiocarbamates, thiuram vulcanization accelerators or dithiophosphates to the natural latex to ensure that no carcinogens are produced during vulcanization, and the vulcanization accelerators with a small amount of isobutyl substituted groups can be improved to improve the vulcanization sufficiency and monosulfide bond ratio.

Benefits of technology

It significantly reduces the cytotoxicity of natural latex products and improves the heat-resistant aging performance, so that the prepared composite materials have better low toxicity and aging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004030854870000021
    Figure BDA0004030854870000021
  • Figure BDA0004030854870000031
    Figure BDA0004030854870000031
  • Figure BDA0004030854870000051
    Figure BDA0004030854870000051
Patent Text Reader

Abstract

The present invention provides an aging-resistant, low-toxic natural latex composite material, and a preparation method and application thereof. The natural latex composite material of the present invention includes components calculated according to the following weight parts: 100 parts of natural latex, 0.7-1.5 parts of vulcanizing agent; 1.0-2.0 parts of vulcanization accelerator; 0-1.5 parts of antioxidant; 0-1.0 parts of active agent; 0-0.5 parts of other additives; wherein the vulcanization accelerator includes at least one vulcanization accelerator containing an isobutyl group and one vulcanization accelerator not containing an isobutyl group. By adding a suitable type of vulcanization accelerator to natural latex for compounding and combining, the production of N-nitrosamine, a substance with a carcinogenic effect, can be greatly reduced, and cytotoxicity can be reduced. At the same time, a small amount of vulcanization accelerator containing an isobutyl substituted group is added to improve the vulcanization performance, so that the prepared composite material has better heat aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, in particular to an aging-resistant and low-toxic natural latex composite material and a preparation method and application thereof. Background Art

[0002] Natural latex products (such as natural latex gloves) are widely used in household life, industry, medical treatment, beauty and other industries. The vulcanization accelerators used in conventional natural latex gloves will indirectly produce carcinogens. That is, during the high-temperature vulcanization process of natural latex gloves, the accelerator will decompose to produce secondary amines, which will react with nitrosating agents such as nitrogen oxides NOx (common in the atmosphere) and nitrites to generate N-nitrosamines, a substance with carcinogenic effects, under certain conditions. Long-term contact with such substances will increase the risk of skin mutation and cancer, which is a potential threat to human health. With the continuous development of various industries, cytotoxicity is related to human health and has gradually become one of the important development trends.

[0003] The existing method to reduce the toxicity of natural latex is to select a suitable vulcanization accelerator. Although the existing added vulcanization accelerator can achieve the purpose of reducing toxicity, its toxicity still needs to be further reduced. In addition, the existing vulcanization accelerator will also cause the natural latex to be insufficiently vulcanized during the processing (vulcanization) process, and the proportion of single sulfur bonds is small, which in turn leads to a decrease in the aging resistance of the product.

[0004] Therefore, it is necessary to provide a natural latex having both good heat aging resistance and lower toxicity. Summary of the invention

[0005] The purpose of the present invention is to overcome the defect of the existing natural latex that the toxicity is reduced while the aging resistance is reduced, and to provide a natural latex composite material that can simultaneously reduce the toxicity of natural latex products and improve the aging resistance. The present invention adds a suitable vulcanization accelerator to the natural latex.

[0006] Another object of the present invention is to provide a method for preparing the natural latex composite material.

[0007] Another object of the present invention is to provide applications of the natural latex composite material in the fields of family life, industry, medical treatment or beauty.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A natural latex composite material, comprising the following components calculated in parts by weight:

[0010]

[0011] The vulcanization accelerator is at least one of a dithiocarbamate accelerator, a thiuram vulcanization accelerator or a dithiophosphate, and the vulcanization accelerator includes at least one vulcanization accelerator containing an isobutyl group and one vulcanization accelerator not containing an isobutyl group.

[0012] The present invention selects at least one of dithiocarbamate accelerators, thiuram vulcanization accelerators or dithiophosphates, which will not produce carcinogens during the vulcanization process, is safe and non-toxic, and can meet the requirements of low toxicity. The inventors of the present invention have further found through a large number of experiments that if the above-mentioned vulcanization accelerator contains a small amount of isobutyl substituent groups, the vulcanization sufficiency of the material and the proportion of single sulfur bonds can be further improved on the basis of ensuring low toxicity, thereby making the prepared aging-resistant and low-toxic natural latex composite material have good heat aging resistance.

[0013] Preferably, the dithiocarbamate accelerator is at least one of zinc dibenzyl dithiocarbamate (ZBEC) or zinc diisobutyl dithiocarbamate (ZDIBC). Among them, ZBEC is a safe secondary amine dithiocarbamate accelerator with excellent anti-scorch performance; ZDIBC is an ultra-fast low-nitrosamine environmentally friendly accelerator.

[0014] Preferably, the thiuram vulcanization accelerator is at least one of diisobutylthiuram disulfide (TiBTD), tetraisobutylthiuram disulfide (IT), tetraisobutylthiuram monosulfide (IU), tetraalkylthiuram disulfide (TATD) or tetrabenzylthiuram disulfide (TBzTD). Thiuram vulcanization accelerators do not produce N-nitrosamines, do not cause discoloration, and have good resistance to vulcanization reduction.

[0015] The dithiophosphate (ZDTP) is a non-amine accelerator that does not contain nitrogen in the molecule and has excellent anti-sulfurization reversion properties. The dithiophosphate includes dithiophosphoric acid-O,O-di-C 1-14 Alkyl ester zinc salt.

[0016] The compounding of the above-mentioned multiple vulcanization accelerators can significantly improve the low toxicity and aging resistance of the obtained composite material.

[0017] In the vulcanization accelerator, the weight ratio of the vulcanization accelerator containing isobutyl group: the vulcanization accelerator without isobutyl group = (0.15-0.65): 1.0. Preferably, in the vulcanization accelerator, the weight ratio of the vulcanization accelerator containing isobutyl group: the vulcanization accelerator without isobutyl group = (0.3-0.6): 1.0. In the vulcanization system, containing a small amount of isobutyl group can further improve the aging resistance of the vulcanized product. Outside this ratio range, the improvement of the aging resistance is limited. The weight ratio of the vulcanization accelerator containing isobutyl group: the vulcanization accelerator without isobutyl group is further preferably (0.32-0.45): 1.0.

[0018] Conventional vulcanizing agents can be used in the present invention, including but not limited to sulfur.

[0019] Optionally, the activator is at least one of metal oxides or carbonates, and the addition of the activator can promote the vulcanization accelerator to play its promoting role well. The metal oxide is at least one of zinc oxide or magnesium oxide; and the carbonate is zinc carbonate.

[0020] Optionally, the antioxidant is at least one of an alkyl monophenol antioxidant or a polymerized alkyl polyphenol antioxidant. The alkyl monophenol antioxidant is antioxidant 264 (BHT); the polymerized alkyl polyphenol antioxidant is KY-616.

[0021] In the present invention, other additives may be added as needed, including but not limited to stabilizers. The stabilizer is at least one of polyoxyethylene fatty alcohol ether, potassium hydroxide or casein.

[0022] In the present invention, water is used as a solvent to allow the above raw materials to be fully and evenly dispersed in the solvent, and to allow the auxiliary agents such as the vulcanizing agent, the vulcanization accelerator, the activator, the antioxidant, etc. to be evenly dispersed in the natural latex.

[0023] Preferably, the natural latex composite material comprises the following components calculated in parts by weight:

[0024]

[0025] The preparation method of the natural latex composite material comprises the following steps:

[0026] According to the formula, natural latex, vulcanizing agent, vulcanization accelerator, activator and other additives are mixed and vulcanized, and then antioxidants are added and mixed to obtain the natural latex composite material.

[0027] Preferably, the method for preparing the natural latex composite material comprises the following steps:

[0028] S1. Mix natural latex and other additives and heat them to 40-43°C to fully dissolve them to obtain a natural latex mixed solution;

[0029] S2. Add a vulcanizing agent, a vulcanization accelerator, and an activator to the natural latex mixed solution obtained in step S1. and mix them, heat the mixture to 45 to 52° C. at a heating rate of 0.03 to 0.2° C. / min, and vulcanize for 2 to 6 hours to obtain pre-vulcanized natural latex;

[0030] S3. Add an antioxidant to the pre-vulcanized natural latex obtained in step S2., mix the mixture, and allow to stand for 3 to 6 days to obtain the natural latex composite material.

[0031] Preferably, the mixing in step S1. is carried out in a solvent, and the solvent is water.

[0032] Preferably, the heating rate in step S2. is 0.1-0.15°C / min. When the heating rate is increased to a certain extent, the performance of the obtained latex composite material tends to be stable, and further improvement is limited; if the heating rate is too slow, it will increase the time cost.

[0033] Preferably, the vulcanization time in step S2. is 3 to 4 hours.

[0034] The application of the above natural latex composite material in the fields of family life, industry, medical treatment or beauty is also within the protection scope of the present invention.

[0035] Preferably, the natural latex composite material is used to prepare gloves.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The invention can greatly reduce the production of N-nitrosamine, a substance with carcinogenic effect, and reduce cytotoxicity by adding a suitable type of vulcanization accelerator to natural latex. Meanwhile, a small amount of vulcanization accelerator containing isobutyl substituted groups is added to improve the vulcanization performance, so that the prepared composite material has better heat aging resistance. DETAILED DESCRIPTION

[0038] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. Unless otherwise specified, the reagents and materials used in the present invention are commercially available.

[0039] The following raw materials are selected in the embodiments of the present invention:

[0040] Natural latex (NR): TVR, purchased from Huang Chunfa, Thailand;

[0041] Vulcanizing agent: sulfur (S), purchased from Yanqifa Chemical Co., Ltd.;

[0042] Vulcanization accelerator:

[0043] Zinc dibenzyldithiocarbamate (ZBEC) was purchased from Guangzhou Ruishi Biotechnology Co., Ltd.;

[0044] Zinc diisobutyldithiocarbamate (ZDIBC) was purchased from Guangzhou Ruishi Biotechnology Co., Ltd.;

[0045] Diisobutylthiuram disulfide (TiBTD) was purchased from Guangzhou Ruishi Biotechnology Co., Ltd.;

[0046] Tetraisobutylthiuram disulfide (IT) was purchased from Guangdong Zhanlin Chemical Co., Ltd.;

[0047] Tetraisobutylthiuram monosulfide (IU) was purchased from Guangdong Zhanlin Chemical Co., Ltd.;

[0048] Tetraalkylthiuram disulfide (TATD) was purchased from Guangdong Zhanlin Chemical Co., Ltd.;

[0049] Tetrabenzylthiuram disulfide (TBzTD) was purchased from Guangdong Zhanlin Chemical Co., Ltd.;

[0050] Dithiophosphate (ZDTP) was purchased from Guangdong Zhanlin Chemical Co., Ltd.;

[0051] Diphenylguanidine (DPG) was purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.;

[0052] Active Agent:

[0053] Zinc oxide (ZnO) was purchased from Henan Xinzhiyuan Chemical Products Co., Ltd.;

[0054] Zinc carbonate (ZnCO3) was purchased from Henan Xinzhiyuan Chemical Products Co., Ltd.;

[0055] Antioxidants:

[0056] Antioxidant 264 was purchased from Jinan Yeqing Biotechnology Co., Ltd.;

[0057] Antioxidant KY-616 was purchased from Jinan Yeqing Biotechnology Co., Ltd.;

[0058] Stabilizer: casein, commercially available;

[0059] It should be noted that, in the present invention, the above-mentioned other additives (stabilizers) are the same substance in parallel tests.

[0060] Examples 1 to 16

[0061] The embodiments of the present invention provide a series of aging-resistant and low-toxic natural latex composite materials, which are prepared according to the formulas in Tables 1 to 2 and a preparation method comprising the following steps:

[0062] S1. Add natural latex and stabilizer to water and mix well, and heat to 40-43°C to fully dissolve to obtain a natural latex mixed solution;

[0063] S2. Add a vulcanizing agent, a vulcanization accelerator, and an activator to the natural latex mixed solution obtained in step S1. and mix them evenly, heat the mixture to 45 to 52° C. at a heating rate of 0.03 to 0.2° C. / min, and vulcanize for 2 to 6 hours to obtain pre-vulcanized natural latex;

[0064] S3. Add an antioxidant to the pre-vulcanized natural latex obtained in step S2., mix well, and let stand for 3 to 6 days to obtain the aging-resistant and low-toxic natural latex composite material.

[0065] Table 1 Formula (weight parts) and preparation parameters of the composite materials of Examples 1 to 9

[0066]

[0067]

[0068] Note: In the table, A represents a vulcanization accelerator containing isobutyl group, and B represents a vulcanization accelerator without isobutyl group.

[0069] Table 2 Formula (parts by weight) and preparation parameters of the composite materials of Examples 11 to 16

[0070]

[0071] Note: The raw materials and preparation process parameters not listed in Table 2 are the same as those of Example 4 in Table 1.

[0072] Embodiment 17

[0073] This embodiment provides an aging-resistant and low-toxic natural latex composite material, the raw material formula of which is the same as that of Example 4, except that it is prepared according to a method comprising the following steps:

[0074] S1. natural latex, stabilizer, vulcanizer, vulcanization accelerator, activator are sequentially added to water and mixed evenly, and then heated to 48°C at a heating rate of 0.1°C / min, and vulcanized for 4h to obtain pre-vulcanized natural latex;

[0075] S2. Add an antioxidant to the pre-vulcanized natural latex obtained in step S1. and mix well, then let stand for 4 days to obtain the aging-resistant and low-toxic natural latex composite material.

[0076] Comparative Example 1

[0077] This comparative example provides a natural latex composite material, and its raw material formula is different from that of Example 4 in that the vulcanization accelerator "0.256 parts of TiBTD, 0.384 parts of ZBEC, and 0.384 parts of TBzTD" is replaced by "1.024 parts of ZDIBC", that is, all the vulcanization accelerators are vulcanization accelerators containing isobutyl groups.

[0078] Comparative Example 2

[0079] This comparative example provides a natural latex composite material, and its raw material formula is different from that of Example 4 in that the vulcanization accelerator "0.256 parts of TiBTD, 0.384 parts of ZBEC, and 0.384 parts of TBzTD" is replaced by "1.024 parts of ZBEC", that is, the vulcanization accelerator does not contain isobutyl group.

[0080] Comparative Example 3

[0081] This comparative example provides a natural latex composite material, and its raw material formula is different from that of Example 4 in that the vulcanization accelerator "0.256 parts of TiBTD, 0.384 parts of ZBEC, and 0.384 parts of TBzTD" is replaced by "0.256 parts of TiBTD+0.768 parts of diphenylguanidine", that is, although the vulcanization accelerator contains both an isobutyl vulcanization accelerator and a non-isobutyl vulcanization accelerator, the non-isobutyl vulcanization accelerator is diphenylguanidine.

[0082] Performance Testing

[0083] The performance of the natural latex composite materials obtained in the above embodiments and comparative examples was characterized. The natural latex composite materials prepared in the above embodiments were placed in a calcium nitrate solution for dipping and molding and dried to obtain a sample to be tested (the molding and vulcanization processes of each sample were kept consistent). The specific test items, test methods and results are as follows:

[0084] 1. Aging resistance: The sample to be tested is prepared into a dumbbell-shaped standard specimen, and the tensile strength and elongation at break of the specimen are tested at room temperature (25°C) at a tensile speed of 500 mm / min according to the standard "ASTM D412-2016"; after the specimen is aged at 70°C for 16 days, the tensile strength and elongation at break of the aged specimen are tested under the same test conditions, and the reduction rate of the tensile strength and elongation at break is calculated. Taking the reduction rate of tensile strength as an example, the calculation formula is: reduction rate of tensile strength after aging (%) = (initial tensile strength of specimen - tensile strength of specimen after aging) / initial tensile strength of specimen * 100%, the calculation method of the reduction rate of elongation at break is similar to the reduction rate of tensile strength, and the test results are shown in Table 3;

[0085] 2. Cytotoxicity test: Take a sample of a certain weight or corresponding area, rinse it with tap water and distilled water in turn, drain it, cut it into pieces, put it in a test tube and sterilize it at 121.5℃ for 30min, dry it and soak it in RPMI-1640 culture medium for 24h for use. Use MTT detection method to test, and finally use an enzyme marker to measure the absorbance value (λ=570nm), calculate the relative proliferation rate (RGR) by the following formula, and perform toxicity classification: RGR=absorbance value of test group / absorbance value of control group×100%, sample toxicity classification standard: 0 ≥100; 1 ≥80; 2 ≥50; 3 ≥30; 4 ≥0. Sample qualification judgment standard: 0 and 1 are qualified, 2 is comprehensively evaluated in combination with morphological analysis, and 3 to 5 are unqualified.

[0086] The test results are shown in Table 3.

[0087] Table 3 Performance test results of natural latex composite materials obtained in Examples and Comparative Examples

[0088]

[0089] From the above results we can see that:

[0090] The aging-resistant and low-toxic natural latex composite materials prepared in the above embodiments of the present invention have both good low toxicity and aging-resistant properties. Among them, the cytotoxicity level of the aging-resistant and low-toxic natural latex composite materials of the present invention is all level 1, with only mild cytotoxicity, and are all judged to be qualified; after aging at 70°C for 13 days, the reduction rate of the tensile strength of the materials is all below 55%, and can be as low as 1.3%; the reduction rate of the elongation at break is all below 14%, and can be as low as 5.8%.

[0091] The results of Examples 1 to 4 show that when the above components are used within the dosage range of the present invention, the obtained materials have both good low toxicity and aging resistance.

[0092] The results of Examples 4 to 8 and Comparative Examples 1 to 2 show that as the proportion of isobutyl-containing vulcanization accelerators in the vulcanization accelerator increases, the aging resistance of the prepared composite material gradually improves, but the initial mechanical properties (tensile strength and elongation at break) of the composite material will show a trend of first rising and then falling, but the mechanical strength meets the use requirements. Within the above-mentioned suitable range of the present invention, the mechanical strength and aging resistance of the composite material are both good. And the results of Comparative Examples 1 and 2 further show that among the vulcanization accelerators, only the two vulcanization accelerators, i.e., the vulcanization accelerator containing isobutyl and the vulcanization accelerator containing no isobutyl, can obtain a composite material with mechanical strength, aging resistance and low toxicity.

[0093] The results of Examples 4 and 9 to 10 show that as the heating rate increases, the rubber particles are vulcanized unevenly and the proportion of single sulfur bonds decreases, resulting in a downward trend in the aging resistance of the obtained composite material. It can be seen that within the above-mentioned heating rate range of the present invention, the mechanical strength and aging resistance of the obtained composite material are good.

[0094] The results of Examples 4 and 11 to 15 show that by selecting a suitable vulcanization accelerator of the present invention, a natural latex composite material having both excellent low toxicity and aging resistance can be obtained.

[0095] Compared with Example 4, Example 16 does not add additional antioxidants, activators and stabilizers, and the performance of the obtained natural latex composite material is not much different from that of Example 4.

[0096] The results of Example 4 and Example 17 show that the order of adding raw materials will also have a small effect on the performance of the obtained composite material. In Example 17, the vulcanization aids (vulcanizing agent, vulcanization accelerator, activator) are added to the natural latex aqueous solution before heating. During the heating process, the vulcanization aids will be coated on the surface of the natural latex particles, resulting in uneven vulcanization, thereby reducing the mechanical strength and aging resistance of the obtained composite material.

[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A natural latex composite material, characterized in that: The composition includes the following components calculated by weight: Wherein, the vulcanization accelerator is at least one of a dithiocarbamate accelerator, a thiuram vulcanization accelerator or a dithiophosphate, and the vulcanization accelerator includes at least one vulcanization accelerator containing an isobutyl group and one vulcanization accelerator not containing an isobutyl group; In the vulcanization accelerator, the weight ratio of the vulcanization accelerator containing isobutyl group to the vulcanization accelerator not containing isobutyl group is (0.3-0.65):1.

0.

2. The natural latex composite material according to claim 1, characterized in that: In the vulcanization accelerator, the weight ratio of the vulcanization accelerator containing an isobutyl group to the vulcanization accelerator not containing an isobutyl group is (0.3 to 0.6):1.

0.

3. The natural latex composite material according to claim 2, characterized in that: The weight ratio of the vulcanization accelerator containing an isobutyl group to the vulcanization accelerator not containing an isobutyl group = (0.32 to 0.45): 1.

0.

4. The natural latex composite material according to claim 1, characterized in that: The dithiocarbamate accelerator is at least one of zinc dibenzyl dithiocarbamate or zinc diisobutyl dithiocarbamate; the thiuram vulcanization accelerator is at least one of diisobutylthiuram disulfide, tetraisobutylthiuram disulfide, tetraisobutylthiuram monosulfide, tetraalkylthiuram disulfide or tetrabenzylthiuram disulfide; the dithiophosphate is dithiophosphate-O,O-di-C 1-14 Alkyl ester zinc salt.

5. The natural latex composite material according to claim 1, characterized in that: The vulcanizing agent is sulfur; the activating agent is at least one of metal oxides or carbonates; the antioxidant is at least one of alkyl monophenol antioxidants or polymerized alkyl polyphenol antioxidants; the other additives are stabilizers, and the stabilizer is at least one of polyoxyethylene fatty alcohol ether, potassium hydroxide or casein.

6. The natural latex composite material according to claim 5, characterized in that: The active agent is at least one of zinc oxide, magnesium oxide or zinc carbonate.

7. The natural latex composite material according to claim 1, characterized in that: The composition includes the following components calculated by weight:

8. The method for preparing the natural latex composite material according to any one of claims 1 to 7, characterized in that: The steps include: According to the formula, natural latex, vulcanizing agent, vulcanization accelerator, activator and other additives are mixed and vulcanized, and then antioxidants are added and mixed to obtain the natural latex composite material.

9. The method for preparing the natural latex composite material according to claim 8, characterized in that: The mixing temperature is 40-52°C.

10. Use of the natural latex composite material according to any one of claims 1 to 7 in the fields of family life, industry, medical treatment or beauty.

Citation Information

Patent Citations

  • Raw material dry-state proportion and preparation vulcanization process of latex for producing low-nitrosamine condom

    CN102746537A